The Role of Incentives, Emotional Connection, and Organizational Justice in Establishing an Effective Whistleblowing System: An Experimental Study - Wijayanti, Dwi Marlina; Yandra, Fachmi Pachlevi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study examines the role of incentives, emotional connection, and organizational justice in supporting whistleblowing system. This study used 3x2x2 between-subjects experimental design. The participants are 171 accounting and banking students from universities in Yogyakarta, Indonesia, who have an adequate understanding on the duties of a management accountant. The experimental data is processed using ANOVA to compare the mean between the experimental groups. The results indicate that the incentives can encourage individuals to report a fraud on conditions of high emotional relations and low organizational justice. Furthermore, when individuals have low emotional relations and high organizational justice, there is no difference between whistleblowing intention on non-anonymous reporting channels (without incentive) as well as anonymous reporting channels